Antibody-mediated LOX-1 inhibition in patients with residual inflammation after myocardial infarction: a randomized phase 2 trial - O'Donoghue, Michelle L; Morrow, David A; Vavere, Andrea L; Kardassis, Dimitris; Moura, Filipe A; Fagundes, Antonio A De Paiva; Ardissino, Diego; Blaha, Vladimir; Farkouh, Michael E; Kato, Eri; Kimura, Takeshi; Kiss, Robert; et al. (Nature medicine, 2025)
The lectin-like oxidized low-density lipoprotein (LDL) receptor-1 (LOX-1) is a key scavenger receptor for oxidized low-density lipoprotein cholesterol (oxLDL), which promotes inflammation and atherosclerosis. Here we evaluated MEDI6570, an antibody that acts as a LOX-1 antagonist, in a randomized, double-blind, dose-finding study in patients with myocardial infarction (MI) and residual inflammation (high-sensitivity C-reactive protein ≥ 1 mg l-1). At 30-365 days after MI, 423 patients (75 women, 348 men) were randomly allocated to 50 mg, 150 mg or 400 mg MEDI6570 or placebo treatment subcutaneously every 4 weeks for 32 weeks. The primary endpoint, the change in the noncalcified plaque volume in the most diseased coronary segment (NCPVMD) by computed tomography angiography, was not significantly different between placebo and MEDI6570 at any dose. The secondary endpoints, global NCPV and low-attenuation plaque volume, were also not different between placebo and MEDI6570 at any dose (all placebo-adjusted comparisons, P > 0.05). With regard to exploratory endpoints, there were reductions in free soluble LOX-1 (sLOX-1) from baseline by 44.8%, 85.8%, 94.0% and 96.4% in the placebo, 50 mg, 150 mg and 400 mg dose arms, respectively (all placebo-adjusted comparisons P < 0.001). Interleukin-6 (IL-6) levels decreased by 2.9%, -3.0%, 18.9% and 21.5% in the placebo, 50 mg, 150 mg and 400 mg arms, respectively, with substantial placebo-adjusted reductions observed only at 150 mg and 400 mg (P < 0.05). MEDI6570 was well tolerated and rates of serious adverse events were similar in the MEDI6570 and placebo groups. In summary, despite favorable effects on sLOX-1 and IL-6, a LOX-1 inhibitor did not reduce noncalcified coronary plaque volume in patients with residual inflammation after acute MI. EudraCT registration: 2020-000840-75 .